Upaya Meningkatkan Visualisasi dan Hasil Belajar Siswa melalui Media Karton Bekas Snack - Mamba’ul Ulum (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2024)
The experience of researchers providing three-dimensional material so far, most students find it difficult to understand three-dimensional material, especially about space-building webs. Even though researchers have tried to guide students in understanding the concept of geometrical nets by showing sketches, students' learning outcomes have not been as expected. In teaching three-dimensional material, media is needed that can help students understand mathematical concepts, so the teacher should prepare the necessary media. Meanwhile in society, there are many media that can be used as a medium for building materials. For example, used snack cartons. This used cardboard will be used by researchers as a medium for learning building materials. This research belongs to the type of Classroom Action Research (CAR). This research was carried out in two cycles, each cycle consisting of 4 activities, namely planning, action, observing and reflecting. The data collection methods used in this study were the observation method and the test method. Based on the results of the study, the use of used snack cardboard media in learning mathematics with the Cooperative Learning model of the Team Game Tournament (TGT) type on flat-sided building materials, especially cubes and blocks, can improve student visualization, student activities and student learning outcomes. Cycle I know the results of the research that the visualization of students get a percentage of 57.81%. For student learning activities, the score of student activity obtained is 58.33%. While the completeness of student learning outcomes in the first cycle of 43.75%. In the second cycle, the students' visualization increased from the first cycle, namely the percentage of 83.33%. For the value of student learning activities obtained in the second cycle is 81.25%. While student learning outcomes obtained in the second cycle also increased by 76.19%.